Letter from Ilse Wolfsberg to Werner Hochwald, August 1, 1941 - Wolfsberg, Ilse (1941)
Ilse Wolfsberg writes to Werner Hochwald (1910-1989) regarding her fiancé and Werner's brother, Fritz Hochwald (1987-1968). Wolfsberg sends Werner new information necessary to continue working towards obtaining an immigration visa for Fritz, who is interned in the Miranda de Ebro concentration camp in Spain. She updates Werner on the current state of Fritz's case.
Keywords: Wolfsberg, Ilse; Hochwald, Fritz G., 1897-1968; Hochwald, Werner, 1910-1989; Emigration and immigration